2010
DOI: 10.1063/1.3432248
|View full text |Cite
|
Sign up to set email alerts
|

Local formation of HArF in solid argon: Low-temperature limit and thermal activation

Abstract: The H + Ar+ F reaction leading to HArF formation in an argon matrix is studied at temperatures down to 8 K. The effects of the precursor concentration, deuteration, IR light, and deposition temperature as well as thermal activation of this reaction are studied. It is found that HArF molecules are formed slowly but efficiently at 8 K in a photolyzed HF / Ar matrix, supporting the previously reported results. The formation rate of HArF ͑and DArF͒ exhibits a low-temperature limit and enhances at elevated temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…This subject has been reviewed recently by Nemukhin et al 21 and Khriachtchev, Ra¨sa¨nen and Gerber. 22 Lignell et al 61 studied the effects of the precursor concentration, deuteration, IR light, and deposition temperature as well as thermal activation on the H þ Ar þ F reaction leading to HArF formation in an argon matrix. They observed that HArF molecules formed slowly but efficiently at 8 K in a photolyzed HF/Ar matrix.…”
Section: Noble Gas Chemistrymentioning
confidence: 99%
“…This subject has been reviewed recently by Nemukhin et al 21 and Khriachtchev, Ra¨sa¨nen and Gerber. 22 Lignell et al 61 studied the effects of the precursor concentration, deuteration, IR light, and deposition temperature as well as thermal activation on the H þ Ar þ F reaction leading to HArF formation in an argon matrix. They observed that HArF molecules formed slowly but efficiently at 8 K in a photolyzed HF/Ar matrix.…”
Section: Noble Gas Chemistrymentioning
confidence: 99%
“…Previous researches showed that the noble-gas compounds HNgX (X represents a strongly electronegative species, such as a halogen, OH, CN or SH) are stabilized by strong Coulombic attraction within the HNg + and X À ion pair. 10,[44][45][46] To investigate the bonding character of HKrOX (X = F, Cl, Br and I), the Lo¨wdin population analyses of HKrOX (X = F, Cl, Br and I) have been carried out at the MP2 level, and the atomic partial charges are listed in Table 6. From Table 6 it is clear that the O and F atom charges are À0.513 and À0.242 in HKrOF, and the changes are À0.692 and À0.308 with respect to HOF, respectively.…”
Section: Bonding Analysis Of Hkrox (X = F CL Br and I)mentioning
confidence: 99%
“…9 The formation of HArF from the reaction of H + Ar + F in an argon matrix was studied at temperatures down to 8 K. The effects of the precursor concentration, deuteration, IR radiation, and deposition temperature as well as thermal activation on this reaction were studied, showing HArF is formed slowly, but efficiently, at 8 K, supporting previously reported results. 10 The 1 : 1 complexes of HY and HXeY (Y = Cl, Br) with N 2 in a Xe matrix were characterised by infrared spectroscopy. Small blue shifts (ca.…”
Section: Matrix-isolated and Gas-phase Noble-gas Speciesmentioning
confidence: 99%